An examination of changes in muscle thickness, isometric strength and body water throughout the menstrual cycle. (24th November 2020) - Kuehne, Tayla E.; Kataoka, Ryo; Yitzchaki, Noam; Zhu, Wenyuan G.; Vasenina, Ecaterina; Buckner, Samuel L.
Abstract: Purpose: The purpose of this study was to examine the changes in muscle size and strength throughout the menstrual cycle in females and to compare these values to a control group of time‐matched males. Methods: 12 males and 16 females visited the laboratory on four occasions. Measures of muscle thickness (MTH), isometric strength and body water were taken during the menstrual phase, ovulation phase and luteal phase of the menstrual cycle. Males scheduled their visits based on a mock menstrual cycle. In addition, participants were asked to complete 4 sets of biceps curls to volitional failure in one arm to examine swelling during each visit. Results: For MTH there was no interaction ( p = .73); however, there was a main effect for sex with males having higher MTH values compared to females [4.07 (0.67) versus. 2.73 (0.42) cm, ( p < .001)] at all time points. For changes in MTH (swelling) there was no interaction ( p = .28). However, there was a main effect for sex, with males demonstrating greater changes in MTH compared to females [0.53(0.11) versus. 0.40 (0.10) cm, ( p < .001)]. Similarly, for total body water, there was no interaction ( p = .66). However, males had greater total body water compared to females [49.6 (6.8) versus. 32.3(3.9) kg, p < .001)] at all time points. Finally, for isometric strength, there was no interaction ( p = .23). However, there was a main effect for sex. Males had higher isometric strength values compared to females [285 (42) versus. 156(36) N ( p < .001)]. Conclusions: Phase of the menstrual cycle does not appear to influence MTH, isometric strength or total body water.